أثر الودائع المصرفية في القيمة السوقية: دراسة في المصارف الإسلامية العراقية المتداولة في سوق العراق للأوراق المالية للمدة "2004-2020" - عبدالشرع، عقيل شاكر; الخالدي، جبار كريم بلبول (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2024)
يهدف البحث إلى معرفة أثر الودائع المصرفية في القيمة السوقية للمصارف الإسلامية العراقية المتداولة في سوق العراق للأوراق المالية للمدة (2004 -2020) ولغرض تحقيق هدف البحث قمنا بدراسة عينة من المصارف الإسلامية العراقية وبالتحديد المتداولة في سوق العراق للأوراق المالية لتوفير بياناتها المالية للمدة (2004-2020) من خلال تحليل متغيرات البحث، إذ اعتمد البحث المنهج الاستنباطي للجانب النظري والمنهج التحليلي والقياسي للجانب العملي، فضلا عن استخدام البرنامج الإحصائي (Eviews10) للمدة (2004-2020) وتوصل البحث إلى مجموعة من الاستنتاجات أهمها وجود أثر إيجابي للودائع المصرفية الإسلامية في القيمة السوقية للمصارف الإسلامية المتداولة في سوق العراق للأوراق المالية كون هذه الودائع تزيد من قابلية المصارف الإسلامية على زيادة نشاطها الائتماني والاستثماري مما يؤدي إلى تحقيق عوائد مالية لهذه المصارف والذي بدوره يؤدي إلى زيادة القيمة السوقية لها، وأوصت الدراسة بالعمل على نشر الثقافة المصرفية الإسلامية وزيادة الجهود لجذب الودائع المصرفية الإسلامية من خلال تنويع هذه الودائع (جارية، ادخارية، استثمارية) وتوظيفها في زيادة نشاط هذه المصارف بواسطة صيغ التمويل الإسلامية المختلفة. The research aims to know the effect of bank deposits on the market value of Iraqi Islamic banks traded in the Iraq Stock Exchange for the period (2004-2020) and for the purpose of achieving the goal of the research we have studied a sample of Iraqi Islamic banks, specifically contributing to the Iraq Stock Exchange to provide their financial statements for the period (2004- 2020) by analyzing the study variables The research relied on the deductive approach for the theoretical side and the analytical and measurement approach for the practical side, as well as using the statistical program (Eviews10) for the period (2004-2020). The research reached a set of conclusions, the most important of which is the presence of a positive impact of Islamic banking deposits on the market value of Islamic banks traded in the Iraqi market for securities, since these deposits increase the ability of Islamic banks to increase their credit and investment activity, which leads to achieving financial returns for these banks, which in turn leads to an increase its market value, The study recommended workin on spreading the Islamic banking culture and increasing efforts to attract Islamic banking deposits by diversifying these deposits (current, savings, investment)& employing them to increase the activity of these banks through various Islamic financing formulas.
Keywords: المؤسسات المالية -- الخدمات المصرفية -- المصارف الإسلامية -- العراق